Ro60 and La ribonucleoproteins become self-aggregated by cell stress - E. Avalos-Díaz; D. Herrera-; S.H. Sánchez-Rodríguez; R. Herrera-Esparza (PAGEPress Publications, 2011)
Ro is a cellular particle composed by three ribonucleoproteins of 60, 54 and 52 kDa (1-3). Ro60 forms a complex with one of the 1-5 hYRNAs (4). Antigenic properties of Ro were described by Clark in 1969 using autoimmune sera (5), and it is broadly accepted that Ro is recognized by autoantibodies from patients with systemic lupus erythematosus (SLE), subacute cutaneous lupus erythematosus (SCLE), Sjögren's syndrome (SS) and neonatal lupus (6). Complexes of Ro are involved in the transcription quality control of 5S rRNA, Ro60 bind the 5S rRNA inefficient transcribed to be eliminated (7, 8). Ro is expressed broadly in nucleus and cytoplasm of eukaryotic cells (9-11).